LUIS GUTIÉRREZ BARRIO, «El Ateneo de Salamanca (1912-1924)», prólogo de Francisco Blanco Prieto, Salamanca, Salamanca Ciudad de Cultura y Saberes, 2022, 269 pp. - Balcells Doménech, José María (Lectura y signo, 2023)
Reseña